Cytotoxicity of contaminated protection devices used in waste sorting industry - Viegas, Carla (2022)
Introduction - Waste sorting is one of the most critical working environments since waste is frequently contaminated by organic matter that functions as a nutrient substrate to microorganisms. In many occupational environments of the waste industry, workers are exposed during long periods to high concentrations of microbial contamination. Several studies have lately stressed health risks related to those environments. Microbial exposures are the leading inducers of several respiratory health symptoms, such as asthma, a decline in lung function, bronchial hyper-responsiveness, chronic bronchitis, wheeze, and cough. Due to the recognized increased risk of microbiologic agents’ exposure and the need of the employer to protect workers from the exposure risks, the use of Filtering Respiratory Protective Devices (FRPD) is mandatory in the Portuguese waste industry. Some hygienic measures taken by workers (such as where the FRPD is kept when not in use) or even the FRPD frequency replacement can impact the FRPD microbial contamination. Bioaerosols in the waste sorting industry consist of complex mixtures of organic and inorganic dust suspended in the air, including bacteria and endotoxins, fungi and mycotoxins, as well as particles of plant and animal origin. Aim of the study - To our knowledge, this is the FIRST study that will allow characterizing the risk resulting from the FRPD conditions of use and identifying the most suitable risk management measures.